A comprehensive multivariate approach for GxE interaction analysis in early maturing rice varieties - Anshori, Muhammad Fuad; Musa, Yunus; Farid, Muh; Jayadi, Muh; Padjung, Rusnadi; Kaimuddin, Kaimuddin; Huang, Yi Cheng; Casimero, Madonna; Bogayong, Iris; Suwarno, Willy Bayuardi; Sembiring, Hasil; Purwoko, Bambang Sapta; et al. (Frontiers in Plant Science, 2024)
The genotype evaluation process requires analysis of GxE interactions to ascertain the responsiveness of a genotype to various environments, including the development of early maturing rice. However, the concept of interaction is relatively specific to grain yieldproductivity. In contrast, grain yieldproductivity is highly polygenic, so assessment must should be done carried out with multivariate traitsapproaches. Therefore, multivariate assessment in evaluating GxE interactions should be developed, especially for early maturing rice genotypes. The study aims aimed to develop createdevelop a comprehensive multivariate approach to improve the comprehensiveness and responsiveness of GxE interaction analysis. The study was conducted in Bone and Soppeng districts, South Sulawesi, Indonesia, with in two seasons. The study used a randomized complete block design, where replications were nested across two seasons and locations. Two check varieties and five early maturing varieties were replicated three times in each environment. Based on this study, a new approach to GxE interaction analysis based on multiple regression index analysis, BLUP analysis, factor analysis, and path analysis was considered adequate, especially for evaluating early maturing rice. This approach combined days to harvest, biological yield, and productivity grain yield in multiple linear regression with weighting based on the combination of all analysesBLUP heritability, eigenvalues in factor analysis, and direct effects. The effectiveness of the GxE interaction assessment was reflected by high coefficient of determination (R 2 ) and gradient (b) values above 0.8 with gradients aboveand 0.9, respectively. in the GxE interaction assessment, especially in Inpari 13 (determination R 2 =0.9; gradient b=1.05 0.9;1.05), Cakrabuana (R 2 =0.98; b=0.99), and Padjajaran (R 2 =0.95; b=1.07) also have good grain yield with days to harvesting consideration, namely 7.83 ton ha -1 , 98.12 days; 7.37 ton ha -1 , 95.52 days; and 7.29 ton ha -1 , 97.23 days, respectively.. Therefore, this index approach can be recommended in GxE interaction analysis to evaluate early maturing rice genotypes. Furthermore, Inpari 13, Cakrabuana, and Padjajaran are recommended as adaptive early maturing varieties.